2019
DOI: 10.1364/oe.27.000a25
|View full text |Cite
|
Sign up to set email alerts
|

Microlens arrays with adjustable aspect ratio fabricated by electrowetting and their application to correlated color temperature tunable light-emitting diodes

Abstract: We develop a facile, fast, and cost-effective method based on the electrowetting effect to fabricate concave microlens arrays (MLA) with a tunable height-to-radius ratio, namely aspect ratio (AR). The electric parameters including voltage and frequency are demonstrated to play an important role in the MLA forming process. With the optimized frequency of 5 Hz, the AR of MLA are tuned from 0.057 to 0.693 for an increasing voltage from 0 V to 180 V. The optical properties of the MLA, including their transmittance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [ 1–3 ] light‐emitting‐diodes (LEDs), [ 4,5,6,7 ] super‐resolution imaging, [ 8,9,10 ] and artificial compound eyes. [ 11,12,13 ] The demand of MLAs with precise shaping features has increased over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [ 1–3 ] light‐emitting‐diodes (LEDs), [ 4,5,6,7 ] super‐resolution imaging, [ 8,9,10 ] and artificial compound eyes. [ 11,12,13 ] The demand of MLAs with precise shaping features has increased over the last few decades.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, microlens arrays (MLAs) have attracted extensive attention due to their wide applications in various fields such as digital displays, [1][2][3] light-emitting-diodes (LEDs), [4,5,6,7] super-resolution imaging, [8,9,10] and artificial compound used to fabricate micro/nanolens arrays (M/NLAs). [13,28] Zhou et al reported that the diameters of the MLAs fabricated by E-jet printing decreased from 32.45 to 1.59 µm when the inner diameter of the nozzle decreased from 25 to 1 µm.…”
Section: Introductionmentioning
confidence: 99%
“…A structure of a ring remote phosphor layer that surrounds an inverted cone lens encapsulant was proposed. This structure did enhance the lumen output as it can direct the lights excited from the chip straight to the LED surface, which greatly reduced the amounts of lights lost from the light reflection inside the WLED package [19]- [21]. Another study reported the ability of yielding high angular CCT uniformity and stability of a patterned remote phosphor structure having the surrounding area uncoated with phosphors [22].…”
Section: Introductionmentioning
confidence: 99%
“…These days, the conventional light source is not able to meet the requirements of modern applications. Thus, the fourth-generation light source called phosphor-converted white light-emitting diodes (pc-WLEDs) is used as an alternative which can bring better prospects in lighting solutions [1]. Its applications have spread out in many different aspects of human life, including landscape, street lighting, and backlighting.…”
Section: Introductionmentioning
confidence: 99%